The use of tools of business communication culture during business negotiations - Lisenyi, E.; Samoilova, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
The article is devoted to topical issues of business communication culture and highlighting its main components as effective tools for business negotiations. To date, the ability to negotiate and communicate without conflict is important for any employee, the purpose of the article is to analyze the main components, forms, styles of communication, based on this, certain recommendations and prevention of threats that may arise during the conversation are created. The importance of the study lies in the fact that the ability to communicate with people correctly is one of the most important factors for achieving success in business and indicates the intellectual potential of the individual. It is very important for a competent specialist to contribute to the formation of a positive social and psychological climate when conducting dialogues or negotiations. After all, only a calm, balanced, with a high level of culture of business communication leader will be able to gain respect and get along with other interlocutors. Business communication covers many factors, in particular: motivation, organization, planning, decision-making and several elements: transmission, perception, understanding. It is believed that 85% of success in any job depends on the ability to communicate with people, and the remaining percentage is experience in the field of activity. Manners, education, behavior, ability to stay in public - these are the details that people around us pay attention to in the first place, especially business partners. That is why, this paper considers all the factors that will help to understand the culture of business communication, learn how to conduct a conversation delicately, all types, features, styles and technologies of communication are considered.  The article considers the requirements of language communication in a business environment and how a person behaves in relation to his opponent in his verbal and non-verbal communication, as a result of which it was found out which postures, gestures and facial expressions indicate the disinterest of the partner in the negotiations.  Since conflict is one of the forms of communication, the article describes the possible causes of such situations. One of the main features of business speech is regulation or subordination to rules, these restrictions are perceived as generally accepted norms of social behavior and in order to avoid conflict, it is necessary to follow some recommendations.